Archbishop Anselm 1093 - 1109: Bec missionary, Canterbury primate, patriarch of another world - Vaughn, Sally N. (The archbishops of Canterbury series, 2012)
Introduction: Anselm's story through his letters in Lambeth -- The Bec background: a missionary mentality -- Anselm's election: primatial theory -- An old sheep yoked to a wild bull: Anselm and King William Rufus -- Interlude: the death of a king -- Two oxen pulling the plow of the church through the land of England: Anselm and King Henry I -- Pope of another world: the primacy at its height, and the problem of York